Kajian Efektivitas Penegakan Hukum terhadap Kebijakan Perhutanan Sosial di Hutan Kemasyarakatan Desa Giri Madia Lombok Barat - Sanjaya, Gede Agus; Risnain, Muh.; Makrum, Markum (Jurnal Silva Samalas, 2026)
Community forest management in Giri Madia Village, West Lombok, faces legal violations that threaten forest sustainability and community well-being. This study aims to identify the forms of legal violations occurring in community forestry practices, analyze the effectiveness of law enforcement regarding social forestry policies, examine the factors supporting and hindering law enforcement, and formulate more effective management strategies. The study employs a socio-legal approach, gathering data through observation, interviews, questionnaires administered to 80 forest farmer group members, and an analysis of violation reports from the Region I Protected Forest and Timber Management Unit (BKPH Wilayah I). The results reveal both administrative violations—such as the trading of management permits—and criminal violations, such as small-scale land encroachment within protected blocks. Law enforcement was deemed effective, scoring 300 out of 400 based on Soerjono Soekanto’s theory, despite being hampered by limited patrol resources. Supporting factors include community awareness and a culture of deliberation (*musyawarah*), while the primary obstacles are a shortage of personnel and a lack of monitoring facilities. The study’s implications highlight the need to strengthen community-based monitoring and provide economic incentives derived from non-timber forest products to ensure sustainable forest management.